Evaluation of the stability, bioavailability, and hypersensitivity of the omega-3 derived anti-leukemic prostaglandin: Δ(12)-prostaglandin J3. - Avinash K Kudva (PLoS ONE, 2013)
Previous studies have demonstrated the ability of an eicosapentaenoic acid (EPA)-derived endogenous cyclopentenone prostaglandin (CyPG) metabolite, Δ(12)-PGJ3, to selectively target leukemic stem cells, but not the normal hematopoietic stems cells, in in vitro and in vivo models of chronic myelogenous leukemia (CML). Here we evaluated the stability, bioavailability, and hypersensitivity of Δ(12)-PGJ3. The stability of Δ(12)-PGJ3 was evaluated under simulated conditions using artificial gastric and intestinal juice. The bioavailability of Δ(12)-PGJ3 in systemic circulation was demonstrated upon intraperitoneal injection into mice by LC-MS/MS. Δ(12)-PGJ3 being a downstream metabolite of PGD3 was tested in vitro using primary mouse bone marrow-derived mast cells (BMMCs) and in vivo mouse models for airway hypersensitivity. ZK118182, a synthetic PG analog with potent PGD2 receptor (DP)-agonist activity and a drug candidate in current clinical trials, was used for toxicological comparison. Δ(12)-PGJ3 was relatively more stable in simulated gastric juice than in simulated intestinal juice that followed first-order kinetics of degradation. Intraperitoneal injection into mice revealed that Δ(12)-PGJ3 was bioavailable and well absorbed into systemic circulation with a Cmax of 263 µg/L at 12 h. Treatment of BMMCs with ZK118182 for 12 h resulted in increased production of histamine, while Δ(12)-PGJ3 did not induce degranulation in BMMCs nor increase histamine. In addition, in vivo testing for hypersensitivity in mice showed that ZK118182 induces higher airways hyperresponsiveness when compared Δ(12)-PGJ3 and/or PBS control. Based on the stability studies, our data indicates that intraperitoneal route of administration of Δ(12)-PGJ3 was favorable than oral administration to achieve effective pharmacological levels in the plasma against leukemia. Δ(12)-PGJ3 failed to increase histamine and IL-4 in BMMCs, which is in agreement with reduced airway hyperresponsiveness in mice. In summary, our studies suggest Δ(12)-PGJ3 to be a promising bioactive metabolite for further evaluation as a potential drug candidate for treating CML.